523PCo-morbilities and survival of patients initially diagnosed with extensive-stage small cell lung cancer: Impact of hypertension, diabetes and chronic hepatitis B viral infection. (24th November 2019) - Xiu, W; Huang, Y; Zhou, X; Zhou, L; Xue, J; Zhu, J; Huang, M; Peng, F; Liu, Y; Xu, Y; Zhang, Y; Yu, M; et al.
Abstract: Background: The aim of this study was to investigate the impact of main co-morbidities in China: hypertension, type 2 diabetes and chronic hepatitis B viral (HBV) infection on overall survival of patients with extensive-stage small-cell lung cancer (SCLC). Methods: Between 2009 and 2018, patients with pathologically diagnosis of SCLC in our hospital were reviewed, and the extensive stage cases were recruited in present study. Patients were divided into hypertension and non-hypertension, diabetes and non-diabetes, HBV-positive and HBV-negative group. The overall survival (OS) was evaluated using the Kaplan-Meier method and Cox proportional hazard models in each group respectively. This work was approved by the West China Hospital Research Ethics Board. Results: Totally, 1345 SCLC patients were reviewed. 632 patients (46.9%) were confirmed with extensive-stage SCLC and analyzed. The median OS in present study was 14.6 months (95% confidence interval (CI) 13.8-15.4 months). The OS of patients with type 2 diabetes (median 17.3 months, 95% CI 14.9-19.8 months) and HBV infection (median 19.9 months, 95% CI 16.1-23.7 months) were significantly improved, comparing to the patients without diabetes (median 14.2 months, 95% CI 13.4-15.1 months) and HBV infection (median 14.2 months, 95% CI 13.4-15.0 months), respectively (p < 0.05). No significant difference in OS was observed in hypertension and non-hypertension group (median 15.7 vs. 14.4 months, p > 0.05). The prognosis significantly decreased if the patients with type 2 diabetes (HR = 0.78, 95% CI: 0.62-0.99, p = 0.046) and HBV infection (HR = 0.61, 95% CI: 0.45-0.83, p = 0.001), comparing to those patients without diabetes or HBV infection. Conclusions: Present data indicated that the co-morbidities (type 2 diabetes and HBV infection) might be associated with the favorable prognosis in extensive-stage SCLC patients. Prospective studies are warranted to verify our findings. Legal entity responsible for the study: Department of Thoracic Oncology and State Key Laboratory of Biotherapy, Cancer Center, West China Hospital, Sichuan University, Chengdu, PR China. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.